Extrapedagogical support and its influence on english language learning with the students of 8 th years of basic education at Paltas High School of Catacocha city, academic year 2013-2014 - Gallegos Vivanco, Ana Lucía (2015)
The present research work entitled: EXTRAPEDAGOGICAL SUPPORT AND ITS INFLUENCE ON ENGLISH LANGUAGE LEARNING WITH THE STUDENTS OF 8TH YEARS OF BASIC EDUCATION AT PALTAS HIGH SCHOOL OF CATACOCHA CITY, ACADEMIC YEAR 2013-2014, has been made to determine the influence of Extrapedagogical Support on the English language learning. The methods used during the development of the present research work were the scientific, descriptive, analytic-synthetic, and explicative. The survey was applied to two teachers and one hundred and twenty two students. The results of this research were: that the Extrapedagogical Support applied by English teachers is not appropriate, this is because they carry out it without planning and in an informal way, due to that there is not established an extrapedagogical support plan in the educative institution. Consequently, students do not improve the English Language learning